2009
DOI: 10.18251/ijme.v11i1.162
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of a Successful Multicultural Project: CCEP and the Infusion of Internationalization across the University

Abstract: Globalization has resulted in the call for greater diversity and multiculturalism in higher education. In order to achieve its stated goal of preparing students for "responsible global citizenship," one master's university 1 has adopted an infusion model of internationalization. This study examines how the university's Chinese Cultural Exchange Program (CCEP) contributed to those campus efforts to enhance multicultural or global awareness, specifically in regards to faculty and student exchanges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…One way that the increased globalization of business schools is being manifested is by the increase of global statements in mission statements (AACSB, 2011;Bao & Ferrara, 2009;Green, Luu, & Burris, 2008). AACSB conducted an analysis of mission statements from 642 schools (AACSB, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way that the increased globalization of business schools is being manifested is by the increase of global statements in mission statements (AACSB, 2011;Bao & Ferrara, 2009;Green, Luu, & Burris, 2008). AACSB conducted an analysis of mission statements from 642 schools (AACSB, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lorange (2003) stated that having an international professoriate was important in global business schools. Bao and Ferrara (2009) found that faculty who participate in a short-term overseas teaching assignment contribute to their own institutions' internationalization process in teaching, research, and service opportunities. Clark and Arbel (1993) noted that to globalize faculty, universities should require more international faculty exchanges and sabbaticals, have more international faculty members, and use industry professionals with global experience in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Like any academic program involving infusion issues into the curriculum, the support of administrators is necessary otherwise, such could not be institutionalized must more become a policy in the department and college levels. Bao and Ferrara (2009) said that "…globalization has resulted in the call for greater diversity and multiculturalism in higher education" (p. 1). While land-grant universities in the U.S. are in position to implement a globalized curriculum in agriculture, private universities currently are also integrating in their mission statement the need for students to be responsible global citizens (Bao &Ferrara).…”
Section: -55)mentioning
confidence: 99%